ANALISIS PERBEDAAN ANTARA PENGGUNAAN NORMA PENGHITUNGAN PENGHASILAN NETO DAN PEMBUKUAN DENGAN STATUS PKP DAN STATUS nonPKP TERHADAP PPh DAN PPN PENGUSAHA KECIL PADA TOKO REJEKI LAMPUNG - Rudy - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
Small entrepreneurs are gross circulation in one year less than Rp 600,000,000 (six hundredmillion dollars) has four alternatives can be chosen to minimize the burden of income tax and VAT.The fourth alternative is the status of a Deemed nonPKP using Net Income (alternative 1), status asnonPKP using Bookkeeping (alternative 2), the status of PFM that uses Deemed Net Income(alternative 3), status as a PFM that uses Bookkeeping (alternative 4).Based on the above results, it can be concluded that the most beneficial alternative forcompanies is the fourth alternative, namely the status of PFM that uses Bookkeeping. Because thealternative is companies can take into account the cost of the gross circulation and as PFM, thecompany can credit Input Tax (PM) against Output Tax (PK) so as to minimize the burden ofcorporate income tax and VAT.